Electro-Optical Properties of Sputtered Calcium Lead Titanate Thin Films for Pyroelectric Detection - Elham Mafi; Nicholas Calvano; Jessica Patel; Md. Sherajul Islam; Md. Sakib Hasan Khan; Mukti Rana (Micromachines, 2020)
We report the deposition and characterization of calcium lead titanate (PCT) thin films for pyroelectric detectors. PCT films of thicknesses ranging from ~250 to 400 nm were deposited on both silicon and Si/SiN/Ti/Au substrates at 13 mTorr pressure by 200W radio frequency sputtering in an Ar + O2 environment. Substrates were kept at variable temperatures during the deposition. The PCT films were annealed at various temperatures in an O2 environment for 15 min. X-ray diffraction results confirm the polycrystalline nature of these films. Energy dispersive spectroscopy function of scanning electron microscope showed that the films are stoichiometric (Ca0.43Pb0.57) TiO3 (Ca/Ti = 0.5, Pb/Ti = 0.66). Temperature dependence of capacitance, pyroelectric current, and pyroelectric coefficient was investigated for different PCT films. Our results show that films deposited at 550 °C and 600 °C demonstrate better quality and larger values of the pyroelectric coefficient. On the other hand, the capacitance fabricated on the PCT films at 550 °C showed the highest value of pyroelectric current and pyroelectric coefficient which were 14 pA and at 30 °C was ~2 µC/m2K respectively at a higher temperature. In addition, we used density functional theory to determine the atomic and band structure, real and imaginary parts of dielectric constant and refractive index, and absorption and reflection constants with energy.